Соціальні права людини: між конституційною абсолютністю і реальною обмеженістю (на прикладі одного закону) - Яковлєв, О. А. (My University, 2016)
On the basis of some provisions of Law of Ukraine «On amendments and invalidation of some legislative acts of Ukraine» dated December 28, 2014 № 76 the author disclose the problem of the interpretation of p. 3, Art. 22 of the Constitution of Ukraine on the impossibility of narrowing the content and scope of existing rights and freedoms during the adoption of new laws in the context of social rights guaranteeing and due to the political and economic situation in the country. Analyzing the nature of social rights, the practice of the Constitutional Court of Ukraine, international human rights law, the author argues that the interpretation of the mentioned constitutional provision must be based on recognition of the existence of the grounds for reviewing the benefits provided to certain population group based on intelligence, proportionality and non-discriminatory nature of the review. // На підставі деяких положень Закону України «Про внесення змін та недійсність деяких законодавчих актів України» від 28 грудня 2014 р. № 76 Автор розкриває проблему тлумачення р. 3, ст. 22 Конституції України з неможливості звуження змісту та обсягу існуючих прав та свобод під час прийняття нових законів у контексті гарантування соціальних прав та через політичну та економічну ситуацію в країні. Аналізуючи характер соціальних прав, практика Конституційного Суду України, Міжнародне правозаконне право, автор стверджує, що тлумачення зазначеного конституційного забезпечення повинно базуватися на визнанні існування підстав для перегляду переваг, наданих певними Групи населення на основі інтелекту, пропорційності та недискримінаційного характеру огляду.
Social human rights, between legal and real constitutional limitations (on the example of one law)
Keywords: social rights; social benefits; benefits; restrictions of human rights; content and scope of human rights; соціальні права; соціальні виплати; переваги; обмеження прав людини; зміст та обсяг прав людини